THE EFFECT OF TAPE CONCENTRATION ON VOLTAGE AND LIGHT BULB LIFE TIME WAS PRODUCED BY LEATHER WASTE AS AN ALTERNATIVE OF ELECTRICAL ENERGY RESOURCES - Manggala, Agus (Politeknik Negeri Sriwijaya, 2017)
Banana peel is a waste that many found in traditional markets in Indonesia. People throw it away because they feel the banana skin is no longer have benefits. Whereas the potential electricity can be generated from this banana skin waste by fermenting banana peel with tape yeast. To prove the existence of electricity that can be produced from banana peel waste, it is necessary to do this research. The method is to ferment banana peel without using yeast tape, then do the addition of tape yeast with a certain amount, then seen the effect of adding yeast tape variation to the PH value and the resulting electrical performance (voltage and duration) of electrical energy generated. The results of the research with fermentation method between banana peel with tape yeast, the addition of tape yeast cause the lower the value of PH produced, the higher the voltage and the longer time the lamp lights up during the research.